Monitoring and control of industrial sewing machines- research on thread tension behavior in lockstitch machines - Mellero, Patrícia (2017)
Processing textile materials is generally very difficult due to the flexible nature of the material. In industries using sewing as assembly process, most processes rely on human labor, being difficult or even impossible to automate. The relations between machine configuration and adjustment, material properties, and the resulting product quality are also complex. This paper describes current work using an instrumented lockstitch sewing machine to study the dynamics and variations of one of the important process parameters during high-speed sewing of shirts: thread tensions. The objective is study the principles that may allow for an automatic setting of the machines, quality control and for real-time process control. It has been found that differences in material properties result in measurable features of the thread tension signals acquired.